Diseño de cobertura de telecomunicaciones Lte para el sector de Guajalo para la empresa Constructora Daniel Ayala Trt S.A. - Jaramillo Pozo, Paul Richard (2017)
The main objective of this project is to determine the levels of LTE coverage in the Guajalo sector, by means of a Drive Test with the mobile application G-NETTRACK LITE, with which it is possible to carry out coverage tests without greater cost thanks to the possibility of having Built several applications on a single computer such as GPS, scaner, digital maps among others. Thanks to this incorporation of mobile applications, the levels of RSRP, RSRQ and SINR can be evidenced to determine the failures of the LTE network of the cellular operator. In order to corroborate the levels of coverage that is obtained from the Drive Test, a prediction of the current state is made in the program Atoll 3.3.0.7 trial. Based on the data obtained, they are analyzed in coverage parameters of the operator. Once analyzed the data and evidencing problems of coverage in the sector, there are types of solutions to improve the coverage gaps that can be observed in both the Drive Test and the predictions, proceed to select a viable solution, both in the Economic part as in the technique. Subsequently a simulation of the chosen solution is made to solve the problems of coverage that is currently in the sector. Finally, the teams are proposed for the implementation through a technical analysis, determining the feasibility of the project, an economic analysis of equipment costs, labor and materials